Correlation between blood magnesium and calcium concentration in patients treated with an anti-EGFR antibody. Issue 1 (December 2016) - Tsujii, Toshiyasu; Ogaki, Takafumi; Nakae, Kaori; Imai, Kiyotaka; Kise, Daisuke; Tada, Shoji; Ueda, Hiroki; Moriyama, Masahiro
Abstract Background Hypomagnesemia is one of the characteristic side effects of the human anti-epidermal growth factor receptor (EGFR) monoclonal antibodies, cetuximab and panitumumab. The major mechanism of anti-EGFR antibody-related hypomagnesemia is suppression of EGFR-mediated urinary Mg2+ reabsorption in both the renal tubule the intestinal tract. Since Mg2+ is known to affect blood Ca2+ levels through regulation of parathyroid hormone (PTH) secretion, we investigated the correlation between Ca2+ and Mg2+ concentration in blood. Methods Between April 2012 and October 2015, blood Mg2+ and Ca2+ concentrations (albumin corrected value) of 22 colon cancer patients undergoing treatment with either cetuximab or panitumumab at Toyooka Public Hospital were measured simultaneously. Results Hypomagnesemia (of all Grades) was reported in 13 of 22 patients. Two patients had hypomagnesemia of severity > Grade 3. Changes in blood Mg2+ and Ca2+ concentration showed a significant correlation (r2 = 0.7455), which could be expressed using the following equation, Ca2+ concentration = 1.4268 × (Mg2+ concentration) + 7.1126. Conclusion Since the early stages of hypomagnesemia produce no characteristic clinical symptoms, it is easily overlooked until it becomes severe. The investigation results suggest that if low blood Ca2+ concentration (mg/dL) is observed in patients administered anti-EGFR antibodies, early evaluation of blood Mg2+ concentration (mg/dL) and prompt supportive care are required to prevent aggravation of hypomagnesemia.